Spreading the word : the Bible business in nineteenth-century America - Wosh, Peter J. (Ithaca : Cornell University Press, 1994)
Tells how the American Bible Society, a modest antebellum reform agency, responded to cataclysmic social change and grew to be a nonprofit corporate bureaucracy that managed, among other projects, what was one of the largest publishing houses in the United States.
1. A Bible House in the City -- 2. From Civic Humanitarianism to Corporate Benevolence: The Changing Nature of the Board of Managers -- 3. Local Particularism and National Interests: Creating the Agency System, 1816-1830 -- 4. The Limits of Consensus in a Capitalist Metropolis: The Problem of Mariners and "Papists" -- 5. The Limits of Consensus in a Christian Republic: Jacksonians, Baptists, Translators, and Abolitionists -- 6. "Motives of Both Duty and Expediency": Entering the Foreign Field, 1831-1844 -- 7. Making Agents Accountable: Bureaucratization and the Agency System, 1845-1865 -- 8. Race, War, and Sectionalism: Reconstructing the Southern Agencies, 1850-1867 -- 9. Bringing System and Order to the Agency: Bible Work in the Levant, 1854-1889 -- Epilogue: From "Missionary Basis" to "Business Basis"? Isaac Bliss's Strange Lament.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: American Bible Society -- History -- 19th century; Bible -- Publication and distribution -- United States; American Bible Society; American Bible Society; Bible; United States -- Social conditions; United States -- Economic conditions; Bijbelgenootschappen; Geschichte 1800-1900.; Economic history; Social conditions; United States; RELIGION / Institutions & Organizations; HISTORY / United States / 19th Century; History; Electronic books